1992
DOI: 10.1017/s0043174500058124
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Broadleaf Weeds in North Carolina Soybean (Glycine max) Fields

Abstract: Spatial distribution of broadleaf weeds within 14 North Carolina soybean fields was characterized by fitting negative binomial distributions to frequency distributions of weed counts in each field. In most cases, the data could be represented by a negative binomial distribution. Estimated values of the parameter K of this distribution were small, often less than one, indicating a high degree of patchiness. The data also indicated that the population as a whole was patchy. Counts of individual species were posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 10 publications
2
86
0
4
Order By: Relevance
“…In a study of 14 soybean (Glycine max (L.) Merr.) fields in North Carolina, Wiles et al (1992) found that up to 29% of each field's experimental quadrants, measuring 9.1 m by the width of the row spacing, contained no weeds. Using 35 mm aerial photography, Thornton et al (1990) concluded that only 18% of a wheat (Triticum aestivum L.) field was infested with wild oats (Avena fatua L.).…”
Section: Measuring Weed Distributionmentioning
confidence: 98%
See 3 more Smart Citations
“…In a study of 14 soybean (Glycine max (L.) Merr.) fields in North Carolina, Wiles et al (1992) found that up to 29% of each field's experimental quadrants, measuring 9.1 m by the width of the row spacing, contained no weeds. Using 35 mm aerial photography, Thornton et al (1990) concluded that only 18% of a wheat (Triticum aestivum L.) field was infested with wild oats (Avena fatua L.).…”
Section: Measuring Weed Distributionmentioning
confidence: 98%
“…However, for aggregated weed populations, assumptions of equal sample variance do not hold, because the sampling locations are spatially related (Cardina et al, 1995). Later field investigations used a grid-based sampling approach to describe the spatial distribution of weed growth (Marshall, 1988;Mortensen et al, 1993;Wiles et al, 1992). Results showed that weed distributions could generally be characterized with the negative binomial function.…”
Section: Measuring Weed Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of the German reduction program for chemical plant protection, herbicide use needs to be controlled strictly in future and reduced to that considered absolutely necessary (BMVEL 2005). It is generally known that the distribution of weed seedlings in arable fields is heterogeneous (Marshall 1988; Thornton et al 1990;Wiles et al 1992;Mortensen et al 1993;Cardina et al 1995 andJohnson et al 1996). Uniform applications of herbicides are still the standard method of weed control.…”
Section: Introductionmentioning
confidence: 99%